2010
DOI: 10.1093/brain/awq177
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocytes are damaged by neuromyelitis optica immunoglobulin G via astrocyte injury

Abstract: Devic's neuromyelitis optica is an inflammatory demyelinating disorder normally restricted to the optic nerves and spinal cord. Since the identification of a specific autoantibody directed against aquaporin 4, neuromyelitis optica-immunoglobulin G/aquaporin 4 antibody, neuromyelitis optica has been considered an entity distinct from multiple sclerosis. Recent findings indicate that the neuromyelitis optica-immunoglobulin G/aquaporin 4 antibody has a pathogenic role through complementdependent astrocyte toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
138
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(153 citation statements)
references
References 57 publications
9
138
1
4
Order By: Relevance
“…Based on our experience,21, 22, 32 use of recombinant reagents, and detailed controls, neither additional components in human samples, imaging, or transgenic labeling can account for the axonal swellings (for details, see Materials and Methods). Although we cannot exclude a possible direct “by‐stander” attack of activated complement factors or an indirect effect by another cell type,39 the timing, lack of associated pathology, and localization of the axonal changes make these unlikely, and suggest that axonal swelling is the consequence of astrocyte loss. Indeed, this is not entirely surprising,40, 41, 42 given that numerous vital interactions between astrocytes and axons have been documented43, 44, 45, 46: For example, astrocytes are known to scavenge glutamate,47 and excitotoxicity has been implicated in axonal pathology during neuroinflammation 48, 49, 50.…”
Section: Discussionmentioning
confidence: 95%
“…Based on our experience,21, 22, 32 use of recombinant reagents, and detailed controls, neither additional components in human samples, imaging, or transgenic labeling can account for the axonal swellings (for details, see Materials and Methods). Although we cannot exclude a possible direct “by‐stander” attack of activated complement factors or an indirect effect by another cell type,39 the timing, lack of associated pathology, and localization of the axonal changes make these unlikely, and suggest that axonal swelling is the consequence of astrocyte loss. Indeed, this is not entirely surprising,40, 41, 42 given that numerous vital interactions between astrocytes and axons have been documented43, 44, 45, 46: For example, astrocytes are known to scavenge glutamate,47 and excitotoxicity has been implicated in axonal pathology during neuroinflammation 48, 49, 50.…”
Section: Discussionmentioning
confidence: 95%
“…Oxidative stress and glutamate‐mediated excitotoxicity plays an important role in NMOSD pathogeny (Marignier et al., 2010). CSF UA levels could reflect oxidative stress and glutamate‐mediated excitotoxicity in neurological patients (Stover et al., 1997), and it has been suggested (Stover et al., 1997) that increasing oxidative stress is reflected by UA and elevated uric acid levels are associated with glutamate‐mediated excitotoxicity in CSF.…”
Section: Discussionmentioning
confidence: 99%
“…One study also reported internalization of glutamate transporter EAAT2 together with AQP4 (13) and concluded that NMO pathogenesis involves glutamate excitotoxicity by a mechanism involving NMO-IgG-induced internalization of EAAT2 and consequent impairment in glutamate uptake from the extracellular space following neuroexcitation. Marignier et al (15) showed that elevated extracellular glutamate could injure oligodendrocytes in an astrocyte/oligodendrocyte mixed primary cell culture. They suggested glutamate excitotoxicity as a possible cause of demyelination in NMO.…”
Section: Neuromyelitis Optica (Nmo)mentioning
confidence: 99%